PEMBELAJARAN PENGANTAR ILMU EKONOMI: KURVA LAFFER DAN PEMANFAATAN APLIKASI EXCEL - IGMA Dharmakarja; Akhmad Solikin (Universitas Teuku Umar, 2018)
The use of spreadsheet has huge potential to enhace experience and learning quality for students. For this reason, it is not surprising that spreadsheet is widely used as a learning tool in academe. This article discusses the use of Microsoft Excel as a learning tool with application for Laffer curve. The Laffer curve is a popular yet controversial tool so that it is very important for students to learn it in Introduction to Economics course to show relationship between tax rate and tax revenue. With reviewing the exisiting literature it is shown origins and prospects regarding the Laffer curve and the possibility of Microsoft Excel for estimating it. Estimating the existence of the Laffer curve can be easily done, but identification of the optimal tax rate and prerequisites for the optimal rate to achieve are beyond the scope of standard Introduction to Economics textbooks. In addition, using real data to construct the Laffer curve make it possible for the students to firstly expose to regression analysis as well as how to analyse data in real world practice.Keywords: Spreadsheets, Microsoft Excel, Laffer curve, Tax, Introduction to Economics.